2009
DOI: 10.1021/es9003679
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Formation of Halogenated Dioxins from Hydroxylated Polybrominated Diphenyl Ethers (OH-PBDEs) and Chlorinated Derivatives (OH-PBCDEs)

Abstract: The potential photochemical formation of polybrominated and mixed halogenated dibenzo-p-dioxins (PBDDs and PXDDs) from hydroxylated polybrominated and polybrominated/ chlorinated diphenyl ethers (OH-PBDEs and OH-PBCDEs) in aqueous solution was studied. The ortho-hydroxylated BDE47 derivative 6-OH-BDE47, and chlorinated derivatives 3-Cl-6-OH-BDE47, 5-Cl-6-OH-BDE47, and 3,5-Cl-6-OH-BDE47 were photolyzed under sunlight at 45 degrees N latitude in buffered waters, Mississippi River water, Lake Josephine water, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 60 publications
3
73
2
Order By: Relevance
“…Addition of the other ring to ortho-C atoms was much easier, but the favored pathway was the one toward IM40 because this pathway exhibited the lowest In addition to the aforementioned reactions, PBDDs can form through the decomposition of ortho-position OH-PBDEs, as confirmed both experimentally 60 and theoretically. Figure S8 of the Supporting Information depicts the mechanism of PBDDs resulting from four ortho-OH-PBDEs which has been verified experimentally 49 and theoretically. 40,50 Removal of phenoxyl hydrogen atoms led to essential intermediates, which were precursors of PBDDs.…”
Section: Resultsmentioning
confidence: 64%
“…Addition of the other ring to ortho-C atoms was much easier, but the favored pathway was the one toward IM40 because this pathway exhibited the lowest In addition to the aforementioned reactions, PBDDs can form through the decomposition of ortho-position OH-PBDEs, as confirmed both experimentally 60 and theoretically. Figure S8 of the Supporting Information depicts the mechanism of PBDDs resulting from four ortho-OH-PBDEs which has been verified experimentally 49 and theoretically. 40,50 Removal of phenoxyl hydrogen atoms led to essential intermediates, which were precursors of PBDDs.…”
Section: Resultsmentioning
confidence: 64%
“…15) Similarly, two natural formation routes for PBDDs have been proposed enzymatic (bromoperoxidase) dimerization of BPs 16) and photolytic cyclization of OH-PBDEs. 17,18) There are also anthropogenic sources of PBDDs and PBDFs, 19) but the absence of PBDFs in the samples indicated that PBDDs were of natural origin. The same may then be true for the OH-tetraBDD.…”
Section: Sources and Potential E Ectsmentioning
confidence: 99%
“…Such enzymatic formation, catalyzed by haloperoxidase, has been proposed to account for the chlorinated analogues (PCDDs) present in forest soil (Hoekstra et al 1999). In addition, OH-PBDEs may be transformed to PBDDs photochemically (Steen et al 2009) and, hypothetically, enzymatically in vivo (Gribble 2000).…”
Section: Sourcesmentioning
confidence: 99%